Honduras : Third Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility; Request for Waiver and Modification of Performance Criteria; and Financing Assurances Review. (IMF Staff Country Reports; Country Report ;, 2006)
Honduras's Third Review under the Poverty Reduction and Growth Facility and Request for Waiver and Modification of Performance Criteria are discussed. The current stance of monetary and exchange rate policies are broadly appropriate, and financial sector reforms are proceeding. Progress has been made in strengthening monetary operations and the prudential framework. The authorities will introduce measures to control the risk of dollar lending to nondollar earners and to limit the net open foreign exchange position of banks.